2004
DOI: 10.1007/s00464-003-8262-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic appendectomy for complicated appendicitis: an evaluation of postoperative factors

Abstract: The minimally invasive laparoscopic technique is safe and efficacious. It should be the initial procedure of choice for most cases of complicated appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(73 citation statements)
references
References 19 publications
5
64
0
4
Order By: Relevance
“…Surgeons prefer to use LA ever-increasingly also in complicated appendicitis (1,5). During LA, surgeons can make detailed abdominal exploration, and this helps to rule out disorders such as pelvic inflammatory disease, over cyst rupture or intraabdominal abcess that mimick acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons prefer to use LA ever-increasingly also in complicated appendicitis (1,5). During LA, surgeons can make detailed abdominal exploration, and this helps to rule out disorders such as pelvic inflammatory disease, over cyst rupture or intraabdominal abcess that mimick acute appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand many authors do not regard complicated appendicitis to be a contraindication for laparoscopic appendectomy. On the contrary, laparoscopic appendectomy in complicated appendicitis is reported to be safe (Ball et al, 2004;Kapischke et al, 2005;Pedersen et al, 2001;Stolzing et al, 2000;Wullstein et al, 2001) and reduce complication rate (Kapischke et al, 2005;Wullstein et al, 2001). Septic wound complications are reported to be less (Piskun et al, 2001;Stolzing et al, 2000).…”
Section: Diagnostic and Therapeutic Outcomes Of Laparoscopic Appendecmentioning
confidence: 99%
“…Intraabdominal abscesses are reported to be equally frequent (Asarias et al, 2011;Khalili et al, 1999;Wullstein et al, 2001) in the open and the laparoscopic approach. Also laparoscopic appendectomy in complicated appendicitis is supposed to lead to a shorter length of stay (Ball et al, 2004;Johnson et al, 1998;Kapischke et al, 2005;Towfigh et al, 2006) and reduced hospital costs (Johnson et al, 1998). The problem with some comparative studies is the existence of selection bias in patients undergoing laparoscopic or open appendectomy and also the fact that statistical analysis is not always done on an intention-to-treat-basis.…”
Section: Diagnostic and Therapeutic Outcomes Of Laparoscopic Appendecmentioning
confidence: 99%
“…However controversy still exists, particularly in complicated appendicitis (CA) which is described as a perforated appendix with or without abscess formation (3)(4)(5). Some authors suggested that LA has an increased risk of postoperative intraabdominal abscess, and prolonged length of stay in complicated appendicitis (6), but others reported that LA is safe, effective, and should be the initial procedure of choice for complicated appendicitis as well (7,8). We aimed to review our experience with appendicitis to compare OA and LA techniques in children with non-complicated and complicated appendicitis.…”
Section: Introductionmentioning
confidence: 99%